Exploring the Meaning of Local Wisdom through Cloth, Candles, and Night: The Study of Batik Naga Tapa Purbalingga Motif - Mufi Fathuroh; Rizky Setiawan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
The research was conducted to determine and describe Batik Tapa Naga Purbalingga both in terms of motifs, colors, and imprisoned meanings. The method used by researchers in writing this article is descriptive qualitative. While the data obtained using observation, interview, and documentation techniques. Based on the results obtained, it is known that the Naga Tapa Purbalingga batik motifs consist of dragons, buildings, dampars, elephants, birds, squirrels, tigers, deer, beetles, living trees, and plants which all form a pattern. The colors of the tapa naga purbalingga batik are white, brown, and black. While the symbolic colors of the Purbalingga tapa dragon are supernatural powers, power, and strength. While the function of tapa naga Purbalingga batik in ancient times is as the clothes of Purbalingga officials while on duty.